PENGARUH METODE PEMBELAJARAN TUTOR SEBAYA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN SIMPANG WARGA 1 KECAMATAN ALUH-ALUH - Nadya Astuti (Jurnal Terapung : Ilmu - Ilmu Sosial, 2022)
This research was motivated by the low learning outcomes of grade 3 students at SDN Simpang Warga, Aluh-aluh District in Mathematics. This is because the teacher only uses the lecture method in teaching. In this study, researchers applied the peer tutoring method to mathematics learning outcomes. The method used in this research is pre-experimental design with the type of one group pre-test design and the sampling technique of Non Probalility Sampling with the type of purposive sampling. The data mining tool used Paired Sample T-test analysis and regression formula. The results showed that the use of the peer tutoring method was fairly good based on the Paired Sample T-test hypothesis test with a confidence level of 95% Sig. 0.05, it was obtained the results of the t-test pre-test and post-test that the Sig. (2-tailed) 0.001 <0.05 and tcount = 3.956> t table of 2.063 with a significant level of 5% and the linear regression hypothesis test obtained tcount> ttable (2.091> 2.069) and a significance of 0.048 <0.05. This means that H0 is rejected and Ha is accepted, so it can be concluded that there is a significant influence between the peer tutor method on student learning outcomes at SDN Simpang Warga, Aluh-aluh District.Key words: Methods, Peer Tutors, Education, Mathematics, Results, Learning.